Simple method for three-dimensional representation of 2-DE spots using a spreadsheet program - Maurer, Martin H (Journal of proteome research, 2004)
Quantitative protein expression analysis based on two-dimensional gel electrophoresis requires comparison of spot volumes. We describe an algorithm to visualize two-dimensional spot patterns in three dimensions using a spreadsheet program for surface plotting.